Levels of rare earth elements, heavy metals and uranium in a population living in Baiyun Obo, Inner Mongolia, China: A pilot study. (June 2015) - Hao, Zhe; Li, Yonghua; Li, Hairong; Wei, Binggan; Liao, Xiaoyong; Liang, Tao; Yu, Jiangping
Highlights: Representing the first human biomonitoring study carried out in Baiyun Obo deposit. Levels of urinary REE, HMs and U were obtained in a population living in Baiyun Obo. HMs and U in the population increased concomitantly with increasing REE levels. Individual factors such as gender and age contributing to the inter-individual variation. Males and people in the young group were more sensitive to REE, HMs and U exposure. Abstract: The Baiyun Obo deposit is the world's largest rare earth elements (REE) deposit. We aimed to investigate levels of REE, heavy metals (HMs) and uranium (U) based on morning urine samples in a population in Baiyun Obo and to assess the possible influence of rare earth mining processes on human exposure. In the mining area, elevated levels were found for the sum of the concentrations of light REE (LREE) and heavy REE (HREE) with mean values at 3.453 and 1.151 μg g −1 creatinine, which were significantly higher than those in the control area. Concentrations of HMs and U in the population increased concomitantly with increasing REE levels. The results revealed that besides REE, HMs and U were produced with REE exploitation. Gender, age, educational level, alcohol and smoking habit were major factors contributing to inter-individual variation. Males were more exposed to these metals than females. Concentrations in people in the senior age group and those with only primary education were low. Drinking and smoking were associated with the levels of LREE, Cr, Cu, Cd and Pb in morning urine. Hence this study provides basic and useful information when addressing public and environmental health challenges in the areas where REE are mined and processed.